2019
DOI: 10.21276/ijcmr.2019.6.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Role of Computed Tomography in Predicting Severity of Acute Pancreatitis and its Correlation with Clinical Outcome

Abstract: Introduction: CECT is very accurate and sensitive investigation in evaluating the severity of acute pancreatitis and the associated complications.With the help of CT, we can manage the patient of acute pancreatitis by categorising them into mild, moderate and severe cases according to modified CT severity index and predict the clinical outcome as well. CT mainly detects the associated complication such as sterile or necrotic fluid collection, pseudocyst fomation, walled off necrosis, pleural effusion, liver ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In Bader HA et al 15 study, amylase level less than or equal to 210 U/l was seen in 29 (29%) patients and more than 210 U/l in 71 (71%) patients, whereas lipase level less than or equal to 180 U/l in 20 (20%) patients and more than 180 U/l in 80 (80%) patients was seen. Sawarkar K et al 18 in their study observed elevated serum lipase and serum amylase levels in all the cases.…”
Section: Etiology Of Acute Pancreatitismentioning
confidence: 78%
“…In Bader HA et al 15 study, amylase level less than or equal to 210 U/l was seen in 29 (29%) patients and more than 210 U/l in 71 (71%) patients, whereas lipase level less than or equal to 180 U/l in 20 (20%) patients and more than 180 U/l in 80 (80%) patients was seen. Sawarkar K et al 18 in their study observed elevated serum lipase and serum amylase levels in all the cases.…”
Section: Etiology Of Acute Pancreatitismentioning
confidence: 78%